The Role of Tbx20 in Cardiovascular Development and Function - Chen, Yuwen; Xiao, Deyong; Zhang, Lu; Cai, Chen-Leng; Li, Bai-Yan; Liu, Ying (Frontiers in Cell and Developmental Biology, 2021)
Tbx20 is a member of Tbx1-subfamily of T-box containing genes and is known to play a series of fundamental roles in cardiovascular development and homeostasis, as well as cardiac remodeling in response to pathophysiological stresses. Mutations in Tbx20 are widely associated with the complex spectrum of congenital heart defects (CHDs), which includes defects in chamber septation, chamber growth, and valvulogenesis. In addition, genetic variants of TBX20 are associated with dilated cardiomyopathy and heart arrhythmia. This broad spectrum of cardiac morphogenetic and functional defects is likely due to its broader expression pattern in multiple cardiogenic cell lineages and its critical regulation of transcriptional networks during cardiac development. In this review, we summarize recent findings in our general understanding of the role of Tbx20 in regulating several important aspects of cardiac development and homeostasis, and heart function.